Remembranza de las Bienales internacionales de video del MAMM 1986-1992: ¿un capítulo olvidado en la historia de Colombia? (2020)
From 1986 to 1992, the Museum of Modern Art of Medellín, held the international video biennials, these are considered the most important video events held in the history of Colombia, however, despite its importance, this event, disappeared from the country's art history. The present investigation argues that the MAMM international video biennials embodied the continuation of the purpose and effort of the private companies from Antioquia to spread contemporary art in the region and make Medellín an international cultural reference. However, as they evolved hand in hand with the dynamics of the Antioquia capital, these biennials found their end with the height of violence associated with drug trafficking in Medellín, the main consequence of which was the obstruction of the museum's finances and the end of the investment.